Experiences with alternative online lectures in medical education in obstetrics and gynecology during the COVID-19 pandemic-possible efficient and student-orientated models for the future? - Riedel, Maximilian; Eisenkolb, Gabriel; Amann, Niklas; Karge, Anne; Meyer, Bastian; Tensil, Maria; Recker, Florian; Dobberkau, Anna Maria; Riedel, Fabian; Kuschel, Bettina; Klein, Evelyn (Archives of Gynecology and Obstetrics, 2022)
PURPOSE: The onset of the COVID-19 pandemic posed an eminent challenge for medical teachers worldwide. Face-to-face lectures and seminars were no longer possible, and alternatives had to be found. E-learning concepts quickly emerged as the only practicable solutions and also offered the opportunity to evaluate whether traditional face-to-face lectures could be translated into an online format, independent of the COVID-19 pandemic. METHODS: We offered an e-learning program consisting of lecture notes, screencasts with audio narration, and online webinars that covered topics normally taught in traditional lectures and seminars. To evaluate the learning behavior and quality of our e-learning program, we drafted a questionnaire that students completed at the end of the 2020 summer semester that had been designed to enable a comparative analysis of the different e-learning modules. RESULTS: Voluntary participation in the online courses was high. Survey analysis revealed high satisfaction with and a distinctive preference for the format, even under regular, COVID-19-independent conditions. In general, a positive appraisal of e-learning-especially as a substitute for regular lectures-was found. Students also reported higher studying efficiency. Exam results were equal to those of previous semesters. CONCLUSION: Both acceptance of and satisfaction with our e-learning modules were high, and students displayed increased demand for this kind of e-learning format. We, therefore, conclude that e-learning offerings could serve as reasonable, efficient, student-orientated substitutes for certain medical courses, especially lectures. These curricular adaptations would correlate with the high digitalization seen in students' everyday lives. This correlation may also hold true independent of the ongoing COVID-19 pandemic.
EVALuna2:487744